Cover Image, Volume 88, Issue 6. (June 2018) - Abbara, A.; Islam, R.; Clarke, S.A.; Jeffers, L.; Christopoulos, G.; Comninos, A.N.; Salim, R.; Lavery, S.A.; Vuong, T.N.L.; Humaidan, P.; Kelsey, T.W.; Trew, G.H.; et al.
Abstract : The cover image, by A. Abbara et al., is based on the Original Article Clinical parameters of ovarian hyperstimulation syndrome following different hormonal triggers of oocyte maturation in IVF treatment, DOI:10.1111/cen.13569 .